2010
DOI: 10.1111/j.1365-2672.2010.04842.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a modified rotating disk reactor for the cultivation of Staphylococcus epidermidis biofilm

Abstract: Aims:  The purpose of this study was to develop a system that would allow biofilms to be cultivated under strictly defined conditions in terms of dissolved oxygen, fluid shear and to assess whether the method was suitable for the detection of respiratory activity stratification in biofilm samples. Methods:  The system is a modified version a commercially available laboratory biofilm reactor and incorporates a number of features such as the provision of defined levels of dissolved oxygen, constant average shear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…S. mutans biofilms were developed on the disks using a rotating disk biofilm reactor (RDR; Biosurface Technologies Corp., Bozeman, MT). This system has been described in detail previously [ 35 ]. The disk was initially incubated for 90 min at 37°C in BHI broth containing a standard cell suspension with stirring at 75 rpm to achieve initial adhesion [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…S. mutans biofilms were developed on the disks using a rotating disk biofilm reactor (RDR; Biosurface Technologies Corp., Bozeman, MT). This system has been described in detail previously [ 35 ]. The disk was initially incubated for 90 min at 37°C in BHI broth containing a standard cell suspension with stirring at 75 rpm to achieve initial adhesion [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Biofilms grown in the CDC biofilm reactor contained less bacteria than those grown in the well plate; therefore, we suggest that the dynamic condition negatively influenced the adherence of bacteria. Fonseca and Sousa [ 18 ] noted that shear strength had a negative effect on the adherence of Pseudomonas aeruginosa in the presence of antibiotics, and Cotter et al [ 19 ] identified a negative correlation between rotational speed and Staphylococcus epidermidis biofilm quantities. Our report agrees with their results, even though their reports were not about periodontal pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…This method was subsequently developed into the standardized biofilm method ASTM E2196-17 [107] that describes the assessment of a P. aeruginosa biofilm grown with shear and continuous flow. For example, Cotter et al [145] tested the ability of S. epidermidis biofilm to grow on polyethylene coupons by the RD reactor. Barry et al [146] used the RD reactor to accelerate biofilm formation on latex samples from an external male catheter.…”
Section: In Vitro Methods To Culture Biofilm On Anti-biofilm Polymmentioning
confidence: 99%